(untitled) (Wudil Journal of Science and Technology Education, 2025)
Several epidemiological studies have shown an inverse relationship between the level of fitness and cardiovascular risk profile in adult population and have also reported that endurance training in this population can reduce the risk factors. The objective of this study was to determine the effect of eight week continuous aerobic exercise on body composition variables of male adolescent secondary school (SS) students of G.S.S. Yankatsari, Dawakin Kudu (DKD) Local Government Area (LGA), Kano State. Population consisted of all the adolescent boys between the ages of 14-18years (n =1,200) in G.SS Yankatsari DKD. 60 male adolescent were randomlysampled and assigned into A&B 30 each. Group were subjected into 8-weeks continuous aerobic exercise (n=30) which is low training modes, of continuous aerobic exercise. it preceded by warm up activities including running, jumps, side Stretch, waist bend, and brisk walking with a view to elevate the body temperature and physiological functions. while B group (n=30) as control. Anthropometric profiles measured were % BF, FP and LBM. null hypotheses were formulated and tested at an alpha level of 0.05. Analysis of Variance One way (ANOVA) determined the significant differences between the 2 groups. Result revealed that 8-week continuous aerobic exercise elicited significant changes in body composition by improving (reduced) % BF of the Experimental group from (9.4105±2.14to 5.49±1.39), it also significantly changes body composition by improving (decreased) the body FP of the Experimental group from (41.7435±.18 to 41.4160±108) and improve LBM (42.13±7.99 to 41.7±18) compared to control group. Kano State ministry of Education should collaborate with Health professionals and exercise scientiststo help create additional services to adolescent students in schools with a view to engage in exercises for maintaining desirable body composition which can lead to healthier living.